Brentanian Continua - Massin, Olivier (My University, 2018)
Brentano’s theory of continuity is based on his account of boundaries. The core idea of the theory is that boundaries and coincidences thereof belong to the essence of continua. Brentano is confident that he developed a full-fledged, boundary-based, theory of continuity; and scholars often concur: whether or not they accept Brentano’s take on continua they consider it a clear contender. My impression, on the contrary, is that, although it is infused with invaluable insights, several aspects of Brentano’s account of continuity remain inchoate. To be clear, the theory of boundaries on which it relies, as well as the account of ontological dependence that Brentano develops alongside his theory of boundaries, constitute splendid achievements. However, the passage from the theory of boundaries to the account of continuity is rather sketchy. This paper pinpoints some chief problems raised by this transition, and proposes some solutions to them which, if not always faithful to the letter of Brentano’s account of continua, are I believe faithful to its spirit. §1 presents Brentano’s critique of the mathematical account of the continuous. §2 introduces Brentano’s positive account of continua. §3 raises three worries about Brentano’s account of continuity. §4 proposes a Neo-Brentanian approach to continua that handles these worries.
Keywords: Brentano Continuity Continua Gunk Boundaries Ontological dependence continuous variation points metaphysics ontology